2023
DOI: 10.1038/s41422-023-00844-w
|View full text |Cite
|
Sign up to set email alerts
|

α-myosin heavy chain lactylation maintains sarcomeric structure and function and alleviates the development of heart failure

Abstract: The sarcomeric interaction of α-myosin heavy chain (α-MHC) with Titin is vital for cardiac structure and contraction. However, the mechanism regulating this interaction in normal and failing hearts remains unknown. Lactate is a crucial energy substrate of the heart. Here, we identify that α-MHC undergoes lactylation on lysine 1897 to regulate the interaction of α-MHC with Titin. We observed a reduction of α-MHC K1897 lactylation in mice and patients with heart failure. Loss of K1897 lactylation in α-MHC K1897R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…Yang et al provided the landscape of H3K23la, H3K18la, and pan-Kla in oocytes and embryos in mice; interestingly, contrary to our hypothesis, hypoxia in vitro decreases histone lactylation, which affects embryonic development . Recently, Zhang et al found that the lactylation of α-myosin heavy chain K1897la in the mouse heart regulates cardiac pacing by affecting the connection to titin . Myosin is present in all types of muscles, including skeletal muscle, and it can be phosphorylated and acetylated in muscle, which also provides a reference for studying animal muscles.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…Yang et al provided the landscape of H3K23la, H3K18la, and pan-Kla in oocytes and embryos in mice; interestingly, contrary to our hypothesis, hypoxia in vitro decreases histone lactylation, which affects embryonic development . Recently, Zhang et al found that the lactylation of α-myosin heavy chain K1897la in the mouse heart regulates cardiac pacing by affecting the connection to titin . Myosin is present in all types of muscles, including skeletal muscle, and it can be phosphorylated and acetylated in muscle, which also provides a reference for studying animal muscles.…”
Section: Introductionmentioning
confidence: 71%
“…151 As a member of the HDAC family, HDAC11 maintains the dryness of hepatocellular carcinoma through glycolysis, and it may also influence lactate levels to some extent. 149 No lactylation research on economic animals has been reported, and studies have mainly focused on humans, mice, and plants. 152,153 Current reports on lactylation focus on areas with abnormal glycolysis, such as tumors.…”
Section: Succinylationmentioning
confidence: 99%
See 2 more Smart Citations
“…One major discovery in the sirtuin field has been that many sirtuins each possesses multiple deacylase activities acting on N ε ‐acyl‐lysine substrates with different acyl groups (Figure 1) (Abmayr & Workman, 2019; Anderson et al., 2017; Bheda et al., 2016; Chen et al., 2015; Chio et al., 2023; Colak et al., 2013; Delaney et al., 2021; Dong et al., 2022; Fan et al., 2023; Feldman et al., 2013; Gil et al., 2013; Huang, Zhang, et al., 2018; Ji et al., 2021; Jin et al., 2016, 2023; Li & Zheng, 2018; Liu et al., 2020; Mikulik et al., 2012; Olesen et al., 2018; Rajabi et al., 2018; Ringel et al., 2014; Seidel et al., 2016; Sun et al., 2022; Tan et al., 2022; Teng et al., 2015; Wang et al., 2023; Zhang et al., 2023; Zhang, Cao, et al., 2019; Zhang, Li, et al., 2019; Zhu et al., 2012; Zu et al., 2022). Specifically, SIRT1/2/3 are all able to catalyze efficiently the deacetylation and defatty‐acylation (e.g., demyristoylation) reactions; CobB from certain bacterial strains is able to catalyze the deacetylation and desuccinylation reactions with comparable catalytic efficiency; CobB from Escherichia coli was further found to catalyze the delactylation reaction with comparable catalytic efficiency to its deacetylase activity; SIRT1 is also able to catalyze deformylation reaction albeit being ~6.6‐fold less proficient than its deacetylase activity; SIRT1 was further found to be an in vivo debenzoylase and delactylase; SIRT2 is also able to catalyze debenzoylation, demethacrylation, and de‐4‐oxononanoylation (de‐4‐ONylation) reactions with more or less comparable catalytic proficiency to that of deacetylation; SIRT2 and SIRT3 were also found to possess an in vivo delactylase activity; SIRT3 is also capable of catalyzing proficiently the decrotonylation and de‐β‐hydroxybutyrylation reactions; SIRT4 is able to catalyze proficiently the deglutarylation and de‐3‐methyl‐glutarylation reactions; SIRT5 is able to catalyze proficiently the demalonylation, desuccinylation, and deglutarylation reactions; SIRT6 was found to catalyze both deacetylation and defattyl‐acylation (e.g., demyristoylation) reactions, with the former activity being weaker than the latter activity on isolated protein substrates; however, the former activity can be enhanced when the substrates are core histone proteins present in a nucleosome unit together with double‐stranded DNA (dsDNA), which has been rationalized very recen...…”
Section: Introductionmentioning
confidence: 99%